Pengaruh Temperatur Sintering terhadap Komposit (TiC-25NiCr) terhadap [(Tiâ,â-MOâ,â) 17C-25NiCr] Hasil Pemaduan Mekanik menggunakan Metode Planetary Ball Mill - Alhamidi, Ali; Suryana, .; Hilman, M. Luthfi (TEKNIKA, 2015)
The powder mixtures of Ti, C, Ni, Cr and Mo are processed by powder metallurgy process to form ceramics metals (cermet) and sintered at various temperatures of 700°C, 1000 °C, and 1100°C have been investigated. The preparation sample of the materials using the principle of mechanical alloying for 10 hours with varying molybdenum at 0 and 0,3% XRD analysis shows that there is no consolidated material cermet. However, the formation of TiC with binders NiCr shown occurred. Sample without molybdenum affect size crystallite of TiC and NiCr, the higher temperatures sintering causing size of crystallite TiC size of the less for higher temperatures sintering, while crystallite size of NiCr is much hinger.